Detection of a putative novel genotype of Anaplasma in gray-brocket deer (Mazama gouazoubira) from Uruguay - Félix, Maria L. (2020)
Anaplasmataceae includes the genera Anaplasma, Ehrlichia, Neorickettsia and Wolbachia, comprising a group of obligate intracellular bacteria. The genus Anaplasma has pathogenic species transmitted by ticks of veterinary and human health importance. Wild ungulates such as deer represent important reservoirs and amplifiers of Anaplasmataceae. The interaction between deer and domestic ruminants represents a serious problem due to the transmission of these pathogens through their ectoparasites. In the present study, we investigated the presence of Anaplasmataceae organisms in blood, tissues and tick samples of a gray-brocket deer (Mazama gouazoubira). The specimen was found dead in a farm in northeast Uruguay. PCRs targeting partial regions of 16S rRNA and groESL genes were carried out for Anaplasmataceae DNA detection. Moreover, several ectoparasites were identified: the chewing louse Tricholipeurus albimarginatus, the Neotropical deer louse fly Lipoptena mazamae, and the ticks Haemaphysalis juxtakochi and Rhipicephalus microplus. A consensus sequence of 1274 bp of 16S rRNA was generated for Anaplasma sp. from the M. gouazoubira blood sample. All ticks analysed by PCR assays were negative. No band was detected in any of the samples after PCR targeting groESL gene. Phylogenetic analysis using 16S rRNA partial gene sequences, clustered the putative novel genotype sequence obtained in this study, named Anaplasma sp. genotype Mazama—Uruguay, along with Anaplasma sp. detected in Mazama sp., Mazama americana and Mazama bororo, all deer species from Brazil. Furthermore, this cluster showed to be closely related to Anaplasma bovis sequences obtained from various ruminants and other mammals from several parts of the world. The pathogenicity as well as its infecting potential to other cervids or domestic ruminants is currently unknown. Further studies should be performed in order to characterize this novel species, especially targeting other genes.